2018
DOI: 10.1097/mca.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction with nonobstructive coronary arteries

Abstract: MINOCA represents a challenging group of heterogeneous patients whose clinical characteristics contrast with classical cardiovascular risk factors. Despite lower mortality than MICAD, the commonly attributed low-risk classification for MINOCA may be erroneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…In light of the difficulty in establishing an etiological diagnosis in all patients, and the clinical dilemma in identifying which patients would require a closer follow-up and more aggressive secondary prevention therapy, the prognostic stratification is crucial. Numerous studies have proposed several prognostic markers, but with heterogeneous results -female sex, history of smoking, atrial fibrillation, previous AMI, ST-segment elevation at admission, 18,23 age, diabetes, previous stroke, peripheral arterial disease, chronic obstructive pulmonary disease, neoplasms, reduced ejection fraction, levels of LDL, creatinine and C-reactive protein, 18 and number of coronary arteries with stenosis less than 50%. 24 The GRACE score is an ideal prognostic stratification tool in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the difficulty in establishing an etiological diagnosis in all patients, and the clinical dilemma in identifying which patients would require a closer follow-up and more aggressive secondary prevention therapy, the prognostic stratification is crucial. Numerous studies have proposed several prognostic markers, but with heterogeneous results -female sex, history of smoking, atrial fibrillation, previous AMI, ST-segment elevation at admission, 18,23 age, diabetes, previous stroke, peripheral arterial disease, chronic obstructive pulmonary disease, neoplasms, reduced ejection fraction, levels of LDL, creatinine and C-reactive protein, 18 and number of coronary arteries with stenosis less than 50%. 24 The GRACE score is an ideal prognostic stratification tool in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of any clinically overt specific cause for the acute presentation, the term myocardial infarction with nonobstructive coronary arteries (MINOCA) is used to classify this condition ( 2 ). Conditions frequently associated with such an entity include Takotsubo cardiomyopathy, myocarditis, and cardiac emboli ( 3 ). There is an important overlap between the diagnostic criteria for MINOCA and clinically suspected myocarditis, the diagnosis first assumed in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The KAMIR-NIH study [42] concluded that, in MINOCA patients, old age, traditional symptoms, STE on ECG, Killip Class IV, and diabetes were independent predictors of all-cause death at the 2-year follow-up. Another study [55] revealed that female sex, younger age, STE, atrial fibrillation, and a history of previous MI were independent predictors of MINOCA. A recent study [56] on prognostic risk factors for MINOCA during a 4.5-year follow-up reported that age, hypertension, diabetes, smoking, previous stroke, MI, peripheral vascular disease, COPD, decreased LV ejection fraction, lower total cholesterol levels, and higher creatinine levels were independent predictors of MACE.…”
Section: Predictors Of Outcomementioning
confidence: 99%